Synchronous liver and peritoneal metastases from colorectal cancer: Is cytoreductive surgery and hyperthermic intraperitoneal chemotherapy combined with liver resection a feasible option? - Di Carlo, Sara; Cavallaro, Giuseppe; La Rovere, Francesca; Usai, Valeria; Siragusa, Leandro; Izzo, Paolo; Izzo, Luciano; Fassari, Alessia; Izzo, Sara; Franceschilli, Marzia; Rossi, Piero; Dhimolea, Sirvjo; et al. (Frontiers in Surgery, 2022)
Background: Traditionally, synchronous liver resection, cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for colorectal liver and peritoneal metastases have been contraindicated. Nowadays, the clinical practice has promoted this aggressive treatment in selected cases. The aim of this study was to review surgical and survival results of an extensive surgical approach including cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) and liver resections (LR). Methods: PubMed, EMBASE, and Web of Science databases were matched in order to find the available literature on this topic. The period of the search was limited to ten years (Jan 2010 – Jan 2021). A threshold of case series of 10 patients or more was applied. Results: In the search period, out of 114 studies found about liver and peritoneal metastases from colorectal cancer, we found 18 papers matching the inclusion criteria. Higher morbidity and mortality were reported for patients who underwent such extensive surgical approach if compared with patients who underwent only cytoreductive surgery and Hipec. Also survival rates seem to be worse in the former than in the latter. Conclusion: Role of combined surgical strategy in patients with synchronous liver and peritoneal metastases from colorectal cancer remains controversial. Survival rates as well as morbidity and mortality seem not in favour of this option. More accurate selection of patients as well as more restrictive surgical indications could perhaps help to improve results in this subgroup of patients with limited curative options.